2019
DOI: 10.24059/olj.v11i2.1725
|View full text |Cite
|
Sign up to set email alerts
|

Online vs. Blended Learning: Differences in Instructional Outcomes and Learner Satisfaction

Abstract: This study investigates differences in instructional and learner factors between two groups of learners exposed to online only and blended delivery formats, respectively, in an effort to compare learning outcomes and other instructional variables between online and blended delivery methods. Findings indicated that no significant differences existed in learning outcomes; however, significant differences existed in several instructional and learner factors between the two delivery format groups. Discussions abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
2
8

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(109 citation statements)
references
References 16 publications
2
97
2
8
Order By: Relevance
“…Specifically, although some studies found no significant differences between the course formats in learning outcomes (Lim et al, 2007;Neuhauser, 2010), others found that students reported higher achievements and performance in online learning (Burkhardt, Kinnie, & Cournoyer, 2008;Connolly, MacArthur, Stansfiled, & McLesslan, 2007;Lim, Kim, Chen, & Ryder, 2008;Navarro & Shoemaker, 2000). Moreover, similar results were found in studies, which examined differences in final grades and satisfaction among students who participated in different methods (F2F or online) of the same course.…”
Section: Learning Outcomes In Online Courses Versus F2f Coursesmentioning
confidence: 57%
See 4 more Smart Citations
“…Specifically, although some studies found no significant differences between the course formats in learning outcomes (Lim et al, 2007;Neuhauser, 2010), others found that students reported higher achievements and performance in online learning (Burkhardt, Kinnie, & Cournoyer, 2008;Connolly, MacArthur, Stansfiled, & McLesslan, 2007;Lim, Kim, Chen, & Ryder, 2008;Navarro & Shoemaker, 2000). Moreover, similar results were found in studies, which examined differences in final grades and satisfaction among students who participated in different methods (F2F or online) of the same course.…”
Section: Learning Outcomes In Online Courses Versus F2f Coursesmentioning
confidence: 57%
“…Assignments, as an interactive activity, may better motivate students and engage them with course content as well as better prepare them to get higher grades on the final exam (Chen et al, 2010;Lim et al, 2007). Thus, these results suggest that although differences between online and F2F courses exist, sometimes they may be derived by the course subject and/or its unique characteristics.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations